PENGARUH BUDAYA KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN KARYAWAN SEBAGAI VARIABEL ANTARA (STUDI KASUS PADA KARYAWAN BAGIAN PRODUKSI CETAK SURAT KABAR PT. MASSCOM GRAPHY SEMARANG) - Mahanani, Indah Woro; Lubis, Nawazirul; Widiartanto, Widiartanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Along with the competition among similar companies and so diverse with rapid changes in the roduct and services are issued by the company is obviously very demanding empployee to achieve a good work result in quality and quantity Employee performance is a determining factor for the achievement of corporate goals. Therefore in this research raise work culture, job satisfaction and employee commitment, which pointed out as an important affecting employee performance.The objective of this research is to examine the influence of work culture and job satisfaction on employee performance with employee commitment as intervening variable. The type of this research is explanatory research, with technique of collecting data is interviews which using questionnaire as instrument. The sample in this research were 40 respondents with technique of sampling is census sampling. Using a Likert Scale as the measurment scale. Data analysis in this research used qualitative and quantitative analysis techniques. Quantitative analysis used statistic test there are correlation coefficient test, simple and multiple regeression analysis, the coefficient of determination, a significant test (t and F) and path analysis using SPSS for windows version 16.0. Validity test and reliability test are used to test instrumen of collecting data. Qualitative analysis used to tabel analysis, respondent perception and companies representation.The result of this research approved that work culture (X1) has positive influenced to the employee commitment (Y1) as 51,9%. Job satisfaction (X2) has positive influenced to the employee commitment (Y1) as 49,9%. Employee commitment (Y1) has positive influenced to the employee performance (Y2) as 63%. Work culture (X1) has positive influenced to the employee performance (Y2) as 73%. Job satisfaction (X2) has positive influenced to the employee performance (Y2) as 43,8%. Work culture (X1) and job satisfaction (X2) have positive influenced to the employee commitment (Y1) as 61,7%. Work culture (X1), job satisfaction (X2) and employee commitment (Y1) have positive influenced to the employee performance (Y2) as 79,7%. According to the result of path analysis, the influenced of work culture (X1) to the employee performance (Y2) will be greater if through employee commitment (Y1) as 80,5% and the influenced of job satisfaction (X2) to the employee performance (Y2) will be greater too if through employee commitment (Y1) as 76,4%.Based on the research results, the researchers suggest that the company giving training (in house training) which purpose to upgrade employee’s soft skills like ability to have socialiszation and good team work with partner, courage to making a decision. As a reward to employee can form of except monthly incentive and money which give in every years like reward as like electronic goods. It’s will increase employee’s commitment and performance that employee reach.